Electricity Value Analysis and Market Mechanism Design Under Carbon-Neutral Goal - Haoyong CHEN (发电技术)
Since the goal of "having CO2 emissions peak before 2030 and achieving carbon neutrality before 2060" was put forward, the ninth meeting of the Central Finance and Economics Committee has further proposed the basic ideas and main measures to achieve this goal, especially implementing renewable energy substitution actions, deepening the reform of the power system and building new power systems with new energy as the main power source. These measures will inevitably lead to major adjustments in the generation mix. On the other hand, various negative events in the electricity markets around the world occurred one after another in recent years, which has attracted widespread attention from all the world. The reasons for these events are highly related to the defects of generation mix and electricity market design. On basis of the introduction and cause analysis of typical accidents in the global electricity markets in recent years, this paper focused on the safety risks and diversification of electricity value caused by the changes in generation mix, analyzed the challenges faced by the electricity market designs, and proposed preliminary solutions. Electricity pricing and electricity market design should be based on the law of electricity value. In the context of large-scale integration of renewable energy, electricity not only has capacity value and energy value in traditional electricity markets, but also has various other values such as flexibility, security and resilience, which makes the problem more complicated. This paper carried out a preliminary analysis of these issues.